2005
DOI: 10.1510/icvts.2004.103044
|View full text |Cite
|
Sign up to set email alerts
|

Surgical experience with 77 primary cardiac tumors

Abstract: Surgical excision of benign cardiac tumors is a safe and curative treatment, which is feasible using minimally invasive right thoracotomy approach and provides excellent results. However, therapy of malignant cardiac tumors continues to have a poor prognosis despite individualization of approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
59
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 21 publications
3
59
0
7
Order By: Relevance
“…Myxomas, most common primary cardiac tumors, are usually located in the LA and RA, and are rarely seen in left and right ventricle. As to non-myxomas cardiac tumors, ventricles are the most susceptible chambers, our patients also confirm to the location distribution of relative tumor occurrence as evident in other series (22)(23)(24).…”
supporting
confidence: 89%
“…Myxomas, most common primary cardiac tumors, are usually located in the LA and RA, and are rarely seen in left and right ventricle. As to non-myxomas cardiac tumors, ventricles are the most susceptible chambers, our patients also confirm to the location distribution of relative tumor occurrence as evident in other series (22)(23)(24).…”
supporting
confidence: 89%
“…Bossert et al [3] reported anomalous presentation of cardiac tumors in a study of 77 patients that underwent surgical treatment, with 59 of them presenting myxoma. Among them, 44 were located in the LA, 4 in the right atrium (RA), 10 cases were biatrial and 1 patient had myxoma in the LV.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) Needless to say, the widespread use of TTE as well as TEE has led to earlier diagnosis and treatment of intracardiac tumors. Two-dimensional echocardiography is the optimal noninvasive technique for imaging small masses (<1 cm) or masses arising from the heart valves, since it provides excellent morphological and functional information 1,5) In addition, since Bootsvelt et al 6) first reported the detection of CPE by MDCT, it has been used as a diagnostic tool along with echocardiography and magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%